Post-Awareness Marketing: Rethinking Brand Communication in a Fragmented Market - Agus Sunaryo; Anna Krisdaningsih; Sugeng Eko Yuli Waluyo; Adil Abdillah (Journal of Management and Social Sciences, 2026)
This research examines the transition from brand awareness to brand meaning within saturated digital ecosystems, specifically focusing on how global brands like Pepsi and Apple navigate the "paradox of ubiquity." The objective is to identify the mechanisms through which brand authenticity and cultural resonance cultivate long-term loyalty and prevent product substitution. Utilizing a qualitative analysis of contemporary branding frameworks and case studies, the study demonstrates that mere visibility is insufficient in modern markets; instead, consumers demand a "glass box" alignment between internal corporate culture and external values. Findings reveal that brand authenticity, characterized by continuity and integrity, serves as a critical defense against commoditization by fostering self-congruity between the brand and the consumer's identity. The implications suggest that brand management must pivot toward narrative-driven communication and community-centric strategies that prioritize cultural salience over vanity reach metrics. Ultimately, the study concludes that in the digital age, a brand’s significance in a consumer's life is the primary driver of resilient brand equity.